Pakistan Army Green Book 1991 : Year of the Commanding officer 1991 - Pakistan Army; Editorial Board : Brig. Abdul Rehman; Lt. Col. John Kenneth Williams; Lt. Col. Syed Ishfaq Ali (GHQ, Rawalpindi Pakistan Army, 1991)
The views expressed in this book are those of the authors and not to be taken as the official opinion or policies of the General Headquarters.
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals